Effect of Superheat Temperature on Hardness and Impact Energy of AlMg1SiCu Cast-alloy - Akhyar, Akhyar; Zulfadhli, Zulfadhli; Pahlevi, Muhammad R.; Setyana, Lilik D.; Hasanuddin, Iskandar; Farhan, Ahmad (Archives of Foundry Engineering, 2026)
This study aimed to evaluate the effect of superheat temperature variation on Vickers hardness and Charpy impact energy of AlMg1SiCu cast-alloy. The material used was Al 6061 metal alloy (re-melt) in the form of rectangular bars. This alloy was melted in an electric furnace and cast in a metal mold. The five superheat of liquidus temperatures applied were +50°C, +100°C, +150°C, +200°C, and +250°C. To reduce thermal shock due to the temperature difference between molten metal and the mold, the mold was heated before the casting process. Subsequently, samples for hardness and impact tests were prepared using machine cutting and tested according to ASTM standards. The results showed an increase in hardness and impact energy along with high superheat temperature. This showed that superheat temperature had a significant effect on the mechanical properties of AlMg1SiCu cast-alloy, with higher values contributing to increased hardness and toughness of the material.